2019
DOI: 10.1097/j.pbj.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Congenital muscular torticollis: where are we today? A retrospective analysis at a tertiary hospital

Abstract: Background: The congenital muscular torticollis is characterized by a persistent lateral flexion of the head to the affected side and cervical rotation to the opposite side due to unilateral shortening of the sternocleidomastoid muscle. The majority of the cases resolve with conservative management, with parents/caregivers education and physical therapy. The aim of this study was to assess demographic and clinical characteristics, treatment options, and outcome, amongst infants referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 21 publications
2
30
2
Order By: Relevance
“…Although the etiology of CMT remains unclear, birth trauma 23) , perinatal compartment syndrome 24) , and impairment of the developing SCM caused by intrauterine restrictions [25][26][27] are known causes. In addition, breech presentation, multiple pregnancies, primiparity, and dystocic labor are considered risk factors for CMT 14) . However, in our study, we could not investigate risk factors for CMT such as abnormal fetal positioning, continuous neck rotation in utero, and difficult delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the etiology of CMT remains unclear, birth trauma 23) , perinatal compartment syndrome 24) , and impairment of the developing SCM caused by intrauterine restrictions [25][26][27] are known causes. In addition, breech presentation, multiple pregnancies, primiparity, and dystocic labor are considered risk factors for CMT 14) . However, in our study, we could not investigate risk factors for CMT such as abnormal fetal positioning, continuous neck rotation in utero, and difficult delivery.…”
Section: Discussionmentioning
confidence: 99%
“…If CMT is not treated early, it can affect the child's appearance, and cause visual impairment and neurodevelopmental delay [9][10][11][12][13] .Conservative treatment of CMT includes home stretching and Physical and Rehabilitation Medicine (PRM) intervention. Postural torticollis identified in an early phase can be rapidly resolved with positioning or simple home stretching, but most cases diagnosed after 3-6 months of age or severe type with SCM mass require longterm exercise therapy by PRM physician 14) . Exercise therapy for CMT includes several A c c e p t e d A r t i c l e components, such as manual stretching of SCM muscle, active rotation exercises, positioning and handling, and environmental adaptation, parent/caregiver education 15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 81 AHP may affect normal facial development, and previous studies have shown that most of the patients with congenital AHP have facial asymmetry. 2 29 50 82 83…”
Section: R Esultsmentioning
confidence: 99%
“…The term torticollis is mostly used in other sciences, which is derived from two Latin words: Torquere, meaning twisted and collum, meaning neck. 2 Although torticollis is considered a nonspecific term indicating a head and neck tilt following contracture of the sternocleidomastoid muscle, 3 the term “ocular torticollis” has been commonly used in ophthalmology and vision science since 1914. 4 …”
Section: Introductionmentioning
confidence: 99%